Pre-surgery Factors to Predict Mortality and Major Complications in Coronary Surgery with no Extracorporeal Circulation - Yanier Coll Muñoz; Francisco Javier Vázquez Roche; Dayan García Cuesta; René M. Cabrera Núñez; Claudio R. Pérez Alfonso; Lázaro de la Cruz Avilés (Medisur)
Background: mortality predicting models in cardiac surgery have been created based on certain population groups. It would be important to know their effectiveness in patients who underwent surgery with no extracorporeal circulation and cardioplegic cardiac arrest. Objective: To determine risk factors to predict mortality and major complications in revascularized patients with no use of extracorporeal circulation and to analyze the behaviour of two stratification models of preoperative risk in cardiac surgery. Methods: A prospective observational study conducted from January 2007 to December 2008 at the Cardiology Center of Santa Clara. The sample included 136 patients who underwent coronary artery bypass grafting with no extracorporeal circulation. Variables collected prospectively were the basis to identify. Risk scales Parsonnet and EuroSCORE 97 were calculated for each patient. Their capacity to predict mortality and possible complications was analyzed through ROC curves. Results: Preoperative variables that significantly increased death risk and major complications were: history of chronic obstructive pulmonary disease, history of diabetes mellitus and three vessel coronary artery disease. Conclusions: Parsonnet and Euroscore 97 risk scales are accurate for mortality and major complications prediction in beating heart revascularization.